(3GdeTQhY GdQhi aj efGbH Hfi Ydhis - (3eMeO Hf CHj HcQ Hf CMeO GdMSjfj GdTdj GdNVQej, HGYdhj, LeGd GdOjf,J (B1093 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi TQM HeYGQa GdYdhGQa UOhQ ChdjGFg CeG HYO aEf GdaVGFd hEf cGfJ cKjQI adGeQjI Cf CLdgG GdEfJSGH Zdi SjO GdCfGe hSejJg GdeTQhY GdQhi ai efGbH Hfi Ydhi s
(3BNQgG (B:s
(3hbO GfJgi GdcdGe Ydi GdhLg GdPi TQWfGg hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3cJHJ CSeGA GdeJQLejf HGdLeQIs
(3Ydi GdfSNI JUMjM hebGHdI JeJ SfI (B1152 (3g` s
(3HUOQ GdfSNI JedcGJ ZjQ eDQNI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B59 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B105s
Keywords: (3GdJGQjNs